Proteoglycan 4 reduces friction more than other synovial fluid components for both cartilage-cartilage and cartilage-metal articulation. Issue 6 (June 2021) - Damen, A.H.A.; van Donkelaar, C.C.; Cardinaels, R.M.; Brandt, J.-M.; Schmidt, T.A.; Ito, K.
Summary: Objective: The clinical success of focal metallic resurfacing implants depends largely on the friction between implant and opposing cartilage. Therefore, the present study determines the lubricating ability of the synovial fluid components hyaluronic acid (HA), proteoglycan 4 (PRG4) and a surface-active phospholipid (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, POPC), on the articulation between cartilage and a Cobalt Chromium Molybdenum (CoCrMo) implant surface, compared with two cartilage surfaces. Methods: A ring-on-disk geometry was used to perform repeated friction measurements at physiologically relevant velocities (6 and 60 mm/s) using lubricants with an increasing number of components present. Shear measurements were performed in order to evaluate the viscosity. To ensure that it is clinically relevant to explore the effect of these components, the presence of PRG4 in synovial fluid obtained from primary and revision knee and hip implant surgeries was examined. Results: PRG4 in the presence of HA was found to significantly reduce the coefficient of friction for both cartilage-cartilage and cartilage-CoCrMo interface. This is relevant, as it was also demonstrated that PRG4 is still present at the time of revision surgeries. The addition of POPC had no effect for either configurations. HA increased the viscosity of the lubricating fluid by one order of magnitude, while PRG4 and POPC had no effect. Conclusion: The present study demonstrates the importance of selecting the appropriate lubrication solution to evaluate implant materials with biotribology tests. Because PRG4 is a key component for reducing friction between cartilage and an opposing surface, developing coatings which bind PRG4 is recommended for cartilage resurfacing implants.